Antimicrobial stewardship for acute-care hospitals: An Asian perspective. (19th September 2018) - Apisarnthanarak, Anucha; Kwa, Andrea Lay-Hoon; Chiu, Cheng-Hsun; Kumar, Suresh; Thu, Le Thi Anh; Tan, Ban Hock; Zong, Zhiyong; Chuang, Yin Ching; Karuniawati, Anis; Tayzon, Maria Fe; So, Thomas Man-Kit; Peterson, Lance R.
Abstract: Inappropriate use of antibiotics is contributing to a serious antimicrobial resistance problem in Asian hospitals. Despite resource constraints in the region, all Asian hospitals should implement antimicrobial stewardship (AMS) programs to optimize antibiotic treatment, improve patient outcomes, and minimize antimicrobial resistance. This document describes a consensus statement from a panel of regional experts to help multidisciplinary AMS teams design programs that suit the needs and resources of their hospitals. In general, AMS teams must decide on appropriate interventions (eg, prospective audit and/or formulary restriction) for their hospital, focusing on the most misused antibiotics and problematic multidrug-resistant organisms. This focus is likely to include carbapenem use with the goal to reduce carbapenem-resistant gram-negative bacteria. Rather than initially trying to introduce a comprehensive, hospital-wide AMS program, it would be practical to begin by pilot testing a simple program based on 1 achievable core intervention for the hospital. AMS team members must work together to determine the most suitable AMS interventions to implement in their hospitals and how best to put them into practice. Continuous monitoring and feedback of outcomes to the AMS teams, hospital administration, and prescribers will enhance sustainability of the AMS programs.